Evaluation of a new identification system, Crystal Enteric/Non-Fermenter, for gram-negative bacilli. - Wauters, G (1995)
A total of 505 fermentative and 201 nonfermentative gram-negative bacilli, identified by conventional methods, were tested by the Crystal Enteric/Non-Fermenter ID kit and by the API 20E or API 20NE identification system. The overall correct results for fermenters were 92.9% by the Crystal kit and 89.1% by the API 20E system. The false identifications (genus and species incorrect) accounted for 3.1 and 7.1% for the Crystal and API systems, respectively. For nonfermenters, figures for correct identifications by the two systems were comparable (Crystal, 75.9%; API 20NE, 75.3%) while the API 20NE system gave twice as many incorrect results (13.8%) as Crystal (6.3%); however, Crystal failed to precisely identify several species included in a "miscellaneous" group. The Crystal Enteric/Non-Fermenter system is an easy-to-use kit which compares favorably with other commercial systems.